1947
DOI: 10.1172/jci101786
|View full text |Cite
|
Sign up to set email alerts
|

The Nutritional Requirements for Nitrogen Balance in Surgical Patients During the Early Postoperative Period 1

Abstract: The role of protein nutrition in the convalescence of surgical patients has been emphasized by many authors during the past 15 years, and much of this work has recently been ably reviewed by Lund (1). The observations of Cuthbertson (2), confirmed by Howard and his co-workers (3), that fractures of long bones resulted in a marked negative nitrogen balance which could not be overcome by substantial increases in the protein intake, raised certain questions regarding the possible effects on nitrogen requirements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1956
1956
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Mulholland et al (1943) and Co T u i et al (1944) were able to produce positive nitrogen balance in th e early postoperative period by high nitrogen (20 g/day) and high calory (4000 cal/day) intake in th eir gastrectom ized patients. Riegel et al (1947) and Troell and Wretlind (1961) achieved the same result by lower nitrogen b u t higher calory intake. Holden et al (1957) found th a t postoperative nitrogen loss is due to poor intake of food.…”
mentioning
confidence: 74%
“…Mulholland et al (1943) and Co T u i et al (1944) were able to produce positive nitrogen balance in th e early postoperative period by high nitrogen (20 g/day) and high calory (4000 cal/day) intake in th eir gastrectom ized patients. Riegel et al (1947) and Troell and Wretlind (1961) achieved the same result by lower nitrogen b u t higher calory intake. Holden et al (1957) found th a t postoperative nitrogen loss is due to poor intake of food.…”
mentioning
confidence: 74%
“…The excess nitrogen requirements for large gastrointestinal surgeries were noted. 5 In hypoalbuminemic patients, a reduction in antibody production was measured and responded to supplementation with oral lactalbumin or casein hydrolysate, although the response was not equivalent to that of well-nourished patients. 4 A descriptive study of enhanced infectious and noninfectious complications in hospitalized patients with hypoproteinemia conducted by Rhoads and corroborated by Brunschwig at the University of Chicago 6 steeled Rhoads' determination to find adequate ways of feeding malnourished surgical patients.…”
Section: Early Links Between Malnutrition and Outcomesmentioning
confidence: 99%
“…14 Perhaps his greatest contribution was his persistence and dedication to the goal of IV nutrition despite the many technical and 376 SPENCER AND COMPHER Vol. 27,No. 5 scientific roadblocks and the considerable obstacle presented by the general belief of the medical community that this was a futile and perhaps foolish quest.…”
Section: Rhoads' Key Contributions To Tpnmentioning
confidence: 99%
See 1 more Smart Citation
“…This view probably originated frQm tfie early observations on the metabolic response t& trauma which revealed increased nitrogen losses in the urine (Cuthbertson, 1930) which could not be prevented by eating a diet rich in first-class protein (Cuthbertson, 1942). If measures are taken to provide food over and above the patient's spontaneous appetite, it is possible to reverse the negative nitrogen balance which is a feature of the metabolic response to surgery (Riegel et al, 1947) or burns (Meyer, Hirschfeld & Abbott, 1947).…”
mentioning
confidence: 99%